Establishment and development of international cooperation during criminal proceedings: theoretical and legal stud - Мазур, Т.Р; Щербина, Л.І (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2024)
The article is devoted to the theoretical and legal study of the formation and development of international cooperation during criminal proceedings. The need for it is determined by the tasks facing domestic science in terms of eliminating individual contradictions between the norms of international legal agreements and criminal procedural legislation, which regulate international cooperation in the specified field. The aforementioned actualized the need for a theoretical study of the formation and development of international cooperation during criminal proceedings in a historical context for a better understanding of its current state of legal regulation and promising directions for further improvement. The purpose of the article is to carry out scientific research on the formation and development of international cooperation in criminal proceedings in its historical retrospect. When conducting a scientific search, the authors chose methods of implementation taking into account the defined goal and subject of the research. They are based on the dialectical method of systematic knowledge of actually existing phenomena and processes, as well as theoretical-logical, empirical and special legal methods, which are means of scientific research in the arsenal of legal sciences, used in interconnection and interdependence to ensure comprehensiveness, completeness and objectivity of the conducted research. As a result of the conducted research, a definition of international cooperation in criminal proceedings was proposed, a scientific division of its development into appropriate stages was carried out, the peculiarities of the development of this institute on a global scale and directly for Ukraine were highlighted, and attention was drawn to the importance of the provisions of relevant international legal treaties, which play an important role both in solving the tasks of criminal proceedings and in the evolutionary development of the criminal procedural legislation of democratic states. Key words: fight against crime, international legal agreements, criminal proceedings, international cooperation, international legal assistance, extradition of persons, taking over of criminal proceedings.

Стаття присвячена теоретико-правовому дослідженню становлення та розвитку міжнародного співробітництва під час кримінального провадження. Потреба у ньому зумовлена завданнями, які постають перед вітчизняною наукою в частині усунення окремих суперечностей між нормами міжнародно-правових угод та кримінального процесуального законодавства, якими унормовується міжнародне співробітництво в означеній сфері. Зазначене актуалізувало необхідність теоретичного дослідження становлення і розвитку міжнародного співробітництва під час кримінального провадження в історичному контексті для кращого розуміння його сучасного стану правового регулювання та перспективних напрямів подальшого удосконалення. Метою статті визначено здійснення наукового пошуку становлення та розвитку міжнародного співробітництва у кримінальному провадженні в його історичній ретроспективі. При проведенні наукового пошуку автори обрали методи його здійснення з урахуванням визначеної мети і предмета дослідження. У їх основі діалектичний метод системного пізнання реально існуючих явищ і процесів, а також теоретично-логічні, емпіричні та спеціальні юридичні методи, що є засобами наукового пошуку в арсеналі юридичних наук, які використовувалися у взаємозв’язку і взаємозалежності, що забезпечило всебічність, повноту й об’єктивність здійсненого дослідження. У результаті проведеного дослідження запропоновано визначення міжнародного співробітництва у кримінальному провадженні, здійснено науковий поділ його розвитку на відповідні етапи, виокремлено особливості розвитку цього інституту в загальносвітовому масштабі та безпосередньо для України, а також звернено увагу на важливість положень відповідних міжнародно-правових договорів, які відіграють вагому роль як у вирішенні завдань кримінального провадження, так і в еволюційному розвитку кримінального процесуального законодавства демократичних держав. Ключові слова: боротьба зі злочинністю, міжнародно-правові договори, кримінальне провадження, міжнародне співробітництво, міжнародна правова допомога, екстрадиція особи, перейняття кримінального провадження
Cтановлення та розвиток міжнародного співробітництва під час кримінального провадження: теоретико-правове дослідження